Harnessing the genetic potential of exotic sorghum germplasm for drought resilience in arid regions of Ethiopia - Birhan, Techale; Abajebel, Nezif; Wakjira, Misganu; Mitiku, Tesfaye; Vadez, Vincent; Tadege, Million; Paterson, Andrew H.; Bantte, Kassahun (Frontiers in Plant Science, 2025)
The narrow genetic diversity of modern sorghum varieties indicates that favorable alleles for the breeding process are frequently lacking in elite germplasm. To address this challenge, here, we use a multiparent breeding technique that employs exotic germplasm to introduce new alleles into an elite gene pool with the goal of identifying potential segregants that combine suitable yield and quality with drought resilience components. The genetic materials used consisted of 1,260 backcross-nested association mapping (BCNAM) BC1F4 lines from 13 populations developed by crossing 13 exotic accessions, earlier screened for diverse drought resilience traits, to a locally important elite cultivar (Teshale), also including the 14 parents. The populations (50 to 200 per family) were evaluated using an alpha lattice design at three locations representative of the major sorghum production regions in Ethiopia. Progenies displayed rich variability in most studied traits, with some outperforming existing varieties in most of these traits. Lines, such as 1180, 1373, 1318, and 1, gave the highest average grain yield, outperforming Teshale, the recurrent parent. Lines 1199, 1263, 1101, and 1204 had the shortest average days to flowering making them more suitable to escape moisture stress periods. Progenies originating from high transpiration efficiency (TE) donor parents showed higher grain yields, early flowering, and maturity, while those from donors with high water extraction showed low yields, delayed flowering, and maturity. In general, donor parents IS14556 and IS16044 with high TE seemed effective in conferring drought tolerance-related characters based on high average performance of all lines from these donors and higher frequencies of transgressants among their progenies. These carefully chosen crosses and the BCNAM approach show promise as an effective vehicle to transfer beneficial alleles from exotic sorghum germplasm into Ethiopian elite genetic backgrounds, in particular, toward improving adaptation of this essential staple crop to the severe droughts that endanger regional food security. These findings highlight that sorghum improvement in water-limited areas may profit from use of exotic genetic resources conferring traits, such as transpiration efficiency, coupled with selection for 1,000-seed weight, leaf senescence, plant height, and flowering time.